2020
DOI: 10.1080/1331677x.2020.1805636
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approximation of option prices via TGARCH model

Abstract: An option is a financial contract that can be used to reduce risks in an investment. It is widely known that a fair price of this contract depends significantly on the volatility of an underlying asset price, which may be affected differently by positive and negative information. Therefore, the fair price of option has been studied through various methods. In this research, an analytical formula for European option pricing via the TGARCH model is derived based on an Edgeworth expansion of the density of cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…They revealed that the influence of social variables is weaker than that of financial variables (L opez-Cabarcos et al, 2020). Hongwiengjan and Thongtha (2021) assessed an analytical approximation of option prices using the TGARCH model. For empirical practice, a new efficient method for pricing options in the case of an in-the-money (ITM) option is provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They revealed that the influence of social variables is weaker than that of financial variables (L opez-Cabarcos et al, 2020). Hongwiengjan and Thongtha (2021) assessed an analytical approximation of option prices using the TGARCH model. For empirical practice, a new efficient method for pricing options in the case of an in-the-money (ITM) option is provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Ausloos et al (2020), spot price variability of index futures has been argued out as optimally examined using the TGARCH modelling technique. Hongwiengjan and Thongtha (2021.) also reference the literature to differentiate TGARCH from other asymmetric GARCH techniques such as the EGARCH and GJR-GARCH by positing that the TGARCH focuses on standard deviation (to approximate stock index volatility) as against conditional variance for the other variants. Again, and unlike other studies, we examined if there existed autocorrelation in the return of stocks on the GSE, for how long, and at what time such autocorrelations die out in the stock market.…”
Section: Introductionmentioning
confidence: 99%
“…In risk management, financial institutions often use the volatility of return to measure risk. In asset pricing, the option price depends on a precise forecast of the underlying asset volatility (Hongwiengjan & Thongtha, 2021). In optimal management of asset portfolios, volatility is often used as an indicator to construct optimal portfolio weights.…”
Section: Introductionmentioning
confidence: 99%